Pengaruh Jigsaw dan Course Review Horay Berbantuan Puzzle Pada Pemahaman Konsep Bentuk Akar Kelas X Di MA. Ashri Jember - Anis Fikriyah; Tri Susilaningtyas; Fitriana Eka Chadra (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2017)
Learning is the main activity of the educational process. This research aims to know the existence of Jigsaw Influence and Course Review Horay which is Assisted Puzzle on Understanding Concept of Grade Student Root Class in MA ASHRI Jember. The type of research used is experimental research. Based on the results of data analysis, normality test can be known value significance for data Kolmogorov-Smirnov and Shapiro-Wilk. uentially of 0.2 and 0.07. The result is greater than 0.05. For Homogeneity Test obtained Fhitung 1.5171, Ftabel = 4.14 it appears that Fhitung <Ftabel. This shows that the data of the two variables are homogeneous. For Test Hypothesis (Test t) obtained thitung> ttabel (1,94> 1,66757). This shows that the jigsaw model and course review horay with the help of puzzles have an effect on the students' understanding of mathematical concepts. Keyword : Learning Jigsaw model, CRH Model learning, Concept Understanding